The Declining Fortunes of the Young Since 2000 - Beaudry, Paul; Green, David A.; Sand, Benjamin M. (American Economic Review, 2014)
We document that successive cohorts of college and post-college degree graduates experienced an increase in the probability of obtaining cognitive jobs both at the start of their careers and with time in the labor market in the 1990s. However, this pattern reversed for cohorts entering after 2000; profiles of the proportion of a cohort in cognitive occupations since school completion fall and become flatter with successive cohorts. Since cohort-wage profiles display a similar pattern, these findings appear to fit with a strong increase in demand for cognitive tasks in the 1990s followed by a decline in the 2000s.